The Influence of Empathy and Entrepreneurship Learning on Students' Interest in Becoming Sociopreneurs at the Senior High School Level in Pekanbaru City: A Quantitative Study - Prawira Mahardika; Caska; Almasdi Syahza (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study examines the influence of Empathy and entrepreneurship learning on students' Interest in becoming sociopreneurs at the senior high school level in Pekanbaru City. The study is motivated by the importance of fostering social entrepreneurship character at an early stage, while empirical studies at the secondary education level remain limited. This research employed a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires and analyzed using statistical tests. The findings show that Empathy has a positive and significant effect on students' sociopreneurship Interest, whereas entrepreneurship learning does not. However, both variables simultaneously have a significant influence, accounting for 24.8% of the variation in sociopreneurship Interest. In conclusion, Empathy plays a key role in shaping students' Interest in sociopreneurship, while entrepreneurship learning needs to be strengthened to better support this Interest.